Case report: Detection and treatment of a rare submucosal gland duct adenoma of the esophagus - Zhou, Yu; He, Daoxing; Huang, Zhigang; Chen, Zhaoyi; Zhou, Zheng; Duan, Hui; Xu, Jie (Frontiers in Oncology, 2025)
This article reports a rare case of esophageal submucosal gland duct adenoma (ESGDA). The patient was found to have this tumor after undergoing endoscopy in an outpatient clinic due to occasional tingling while eating. White light endoscopy revealed the tumor as a dumbbell-shaped bulge, and ultrasound endoscopy revealed it as a hypoechoic mass located in the submucosal layer. The tumor was successfully resected by endoscopic mucosal dissection with no postoperative recurrence and a good prognosis. In conjunction with literature analysis, the diagnosis of ESGDA relies mainly on endoscopic and pathologic examinations, and its histologic features are highly specific. Despite the rarity of ESGDA, accurate histologic evaluation is essential to avoid misdiagnosis. Complete endoscopic resection is an effective treatment with a favorable long-term prognosis. Further studies remain necessary to reveal its pathogenesis.